Fast Internet, Women Identity, and Female Genital Mutilation - Jorge Garcia-Hombrados; Daniel Pérez-Parra; Ricardo Ciacci (Institute of Labor Economics (IZA), 2024)
Female Genital Mutilation (FGM) is deeply ingrained in the identity of women in many societies, where it symbolizes feminine traits valued within these communities, such as purity or conformity to the community. This paper examines the impact of the expansion of fast internet, arguably a powerful catalyst for identity transformation. Using Nigeria as a case study, our findings indicate that exposure to fast internet reduces the prevalence of FGM and diminishes support for the practice, particularly among women. The results suggest that the effect is not driven by exposure to online explicit anti-FGM content. Instead, we find evidence of a broader identity transformation among women, with less stigma around promiscuous behaviors and premarital sex - stigmas that are associated with FGM in Nigeria - thereby reducing the social relevance of FGM. Specifically, we show that the expansion of fast internet increased the number of reported sexual partners, decreased age at first sex but not age at marriage, and increased the number of extra-marital relations for women. Conversely, we rule out wealth and migration as major drivers of the effect of fast internet on FGM.
Keywords: O12; J16; O33; 330; female genital mutilation; cultural change; fast internet